Short‐term side effects and attitudes towards second donation: A comparison of related and unrelated haematopoietic stem cell donors. Issue 3 (18th August 2017) - Pahnke, Simon; Larfors, Gunnar; Axdorph‐Nygell, Ulla; Fischer‐Nielsen, Anne; Haastrup, Eva; Heldal, Dag; Itälä‐Remes, Maija; Johansson, Jan‐Erik; Kauppila, Marjut; Lenhoff, Stig; Ljungman, Per; Niittyvuopio, Riita; et al.
Abstract: The Nordic Register of Haematopoietic Stem Cell Donors (NRHSD) has registered related and unrelated donors from 10 transplant centres in Sweden, Norway, Finland and Denmark since 1998. We present a prospective, observational study of 1, 957 donors, focusing mainly on the differences between related and unrelated donors. Related donors are reported to have more comorbidities, but similar side effects compared with unrelated donors. Side effects after BM or PBSC donation are generally of short duration and in this study no deaths, myocardial infarctions, splenic ruptures, or thromboembolic events are reported. Interestingly, related donors express more hesitancy towards donating again when asked 1 month after donation.